O sentido da tolerância religiosa na concepção de estado moderno segundo John Locke - Aguiar Neto, Antônio Severino de (2016)
Religious freedom was one of the most debated topics in the seventeenth century in England. This issue was closely related to the extent of the problem of civil jurisdiction or even the relationship between the civil power and ecclesiastical power. The philosopher of Wrington, John Locke, actively participated in the discussions of the time. He devoted several writings to the subject, including the Charter on Tolerance (1689). Our research suggests that the Lockean tolerance is outlined above all, by political issues and not exclusively religious, as is advocated by many. The issue of tolerance with regard to defense and the preservation of the natural rights of men, called Locke in his Second Treatise on Government, such as the right to property. For this reason, at first, we stop to speak about the civil state, as this will constitute the reference framework for our considerations about tolerance. Then we try to talk about the excessive entanglement, presented by Locke in his Letter, between the religious sphere and politics, which resulted in the full enjoyment of these rights to some and deprivation or denial of these to others. And lastly, we demonstrate that tolerance is not something to be unrestricted grant, for any person or group acting against equal enjoyment and free of natural rights should be excluded from tolerance.